La nascita e lo sviluppo del nesso tryphé-decadenza nella storiografia ellenistica - Livia De Martinis (Erga-Logoi, 2022)
In the 4th century BC Greek historiography abandons the monographic genre to propose a general interpretation of history: a possible interpretative key is that of tryphé, excessive luxury that corrupts and leads to an unstoppable decadence cities, peoples and states. The first theoretical elaboration of the tryphé-decadence nexus occurs in the historiographical work of Ephorus of Cyme and Timaeus of Tauromenium. In later Greek historiography, however, the concept of tryphé remains in most cases connected to a moral judgment, without becoming a true criterion of historical interpretation. And if in this sense it has been too often interpreted by the moderns, this is probably due to the influence on them exerted by the Roman historiography. In it the equivalent of tryphé can be considered the luxuria, understood as corrupting luxury, which since the 2nd century BC would lead to a progressive weakening of Rome and that in the historiographic production sees an insistent connection between the social ethics, precisely corrupt, and the political decadence.